Hubungan Kelerengan Lahan Terhadap Produksi Tandan Buah Segar Kelapa Sawit Di Perkebunan PT. Bina Pratama Sakato Jaya Kabupaten Sijunjung - Miskana; Irfan Suliansyah; Edwin (Jurusan Budidaya Perkebunan, 2022)
Palm oil production in Indonesia must be optimized to meet world market demands. The steeper the slope of the land, the more erosion and weed growth will occur. This can result in disrupted oil palm growth due to erratic competition, air, and light between oil palm and weeds around the plant. This study aims to determine the relationship between the slope of the land with the production level of Fresh Fruit Bunches of oil palm in the PT. Bina Pratama Sakato Jaya Unit Kiliran Jao Sijunjung Regency. The research is in the form of a survey with a purposive random sampling method. Observation parameters consisted of the weight of fresh fruit bunches, the diameter of stem circumference, and plant height. Data processing using a simple linear regression method. The plantation area of ​​PT. Bina Pratama Sakato Jaya is currently 4,678.79 Ha. Slope significantly affects the production of oil palm Fresh Fruit Bunches (FFB). The highest average production was obtained on flat (0-3%) and gentle slopes (3-8%), and the lowest average production on slopes (15-30%) and very steep (30-45%)